Discrepancy between post-treatment infarct volume and 90-day outcome in the ESCAPE randomized controlled trial. Issue 5 (July 2021) - Ganesh, Aravind; Menon, Bijoy K; Assis, Zarina A; Demchuk, Andrew M; Al-Ajlan, Fahad S; Al-Mekhlafi, Mohammed A; Rempel, Jeremy L; Shuaib, Ashfaq; Baxter, Blaise W; Devlin, Thomas; Thornton, John; Williams, David; et al.
Background: Some patients with ischemic stroke have poor outcomes despite small infarcts after endovascular thrombectomy, while others with large infarcts sometimes fare better. Aims: We explored factors associated with such discrepancies between post-treatment infarct volume (PIV) and functional outcome. Methods: We identified patients with small PIV (volume ≤ 25th percentile) and large PIV (volume ≥ 75th percentile) on 24–48-h CT/MRI in the ESCAPE randomized-controlled trial. Demographics, comorbidities, baseline, and 24–48-h stroke severity (NIHSS), stroke location, treatment type, post-stroke complications, and other outcome scales like Barthel Index, and EQ-5D were compared between "discrepant cases" – those with 90-day modified Rankin Scale(mRS) ≤ 2 despite large PIV or mRS ≥ 3 despite small PIV – and "non-discrepant cases". Multi-variable logistic regression was used to identify pre-treatment and post-treatment factors associated with small-PIV/mRS ≥ 3 and large-PIV/mRS ≤ 2. Sensitivity analyses used different definitions of small/large PIV and good/poor outcome. Results: Among 315 patients, median PIV was 21 mL; 27/79 (34.2%) patients with PIV ≤ 7 mL (25th percentile) had mRS ≥ 3; 12/80 (15.0%) with PIV ≥ 72 mL (75th percentile) had mRS ≤ 2. Discrepant cases did not differ by CT versus MRI-based PIV ascertainment, or right versus left-hemisphere involvement ( p  = 0.39, p  = 0.81, respectively, for PIV ≤ 7 mL/mRS ≥ 3). Pre-treatment factors independently associated with small-PIV/mRS ≥ 3 included older age ( p  = 0.010), cancer, and vascular risk-factors; post-treatment factors included 48-h NIHSS ( p  = 0.007) and post-stroke complications ( p  = 0.026). Absence of vascular risk-factors ( p  = 0.004), CT-based lentiform nucleus sparing ( p  = 0.002), lower 24-hour NIHSS ( p  = 0.001), and absence of complications ( p  = 0.013) were associated with large-PIV/mRS ≤ 2. Sensitivity analyses yielded similar results. Conclusions: Discrepancies between functional ability and PIV are likely explained by differences in age, comorbidities, and post-stroke complications, emphasizing the need for high-quality post-thrombectomy stroke care. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT01778335 .